1997
DOI: 10.1108/02686909710180670
|View full text |Cite
|
Sign up to set email alerts
|

Transaction cost economics: a theory for internal audit?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 14 publications
1
45
0
3
Order By: Relevance
“…Sad to say, synthesis that has been conducted by researchers like Boyle (1993) and Spraakman (1997) in their studies is not going adequate consideration to the part played by transaction cost economics.Itcannot be denied the usefulness of transaction cost economics in undertaking the operation cost of companies and this in fact is of great assistance to the manger1990. As Penno (1990) justify this concept as to how internal audit findings can be very objective as and when the hierarchy of the organization is made aware off.…”
Section: Transaction Cost Economicsmentioning
confidence: 99%
“…Sad to say, synthesis that has been conducted by researchers like Boyle (1993) and Spraakman (1997) in their studies is not going adequate consideration to the part played by transaction cost economics.Itcannot be denied the usefulness of transaction cost economics in undertaking the operation cost of companies and this in fact is of great assistance to the manger1990. As Penno (1990) justify this concept as to how internal audit findings can be very objective as and when the hierarchy of the organization is made aware off.…”
Section: Transaction Cost Economicsmentioning
confidence: 99%
“…Dittenhofer (2001) has also observed that if internal audit quality is maintained, it will contribute to the appropriateness of procedures and operations of the auditee, and thereby internal audit contributes to effectiveness of the auditee and the organization as a whole. Using agency theory, Xiangdong (1997) explained the role that internal audit plays in an economy and points out that internal audit has an advantage over external audit in obtaining information quickly and finding problems at an earlier stage; and Spraakman (1997), applying the theory of transaction cost economics, demonstrated how internal audit recommendations are important to the management of government organizations.…”
Section: Internal Audit Effectivenessmentioning
confidence: 99%
“…Prior literature relating to internal audit effectiveness has either focused on the internal audit's ability to plan, execute and objectively communicate useful findings (Xiangdong, 1997;Spraakman, 1997;Dittenhofer, 2001); or taken a broader view and included factors that transcend the boundary of a single organization (Van Gansberghe, 2005). This paper attempts to introduce a new perspective for evaluation of internal audit effectiveness by identifying factors within an organization that impact on audit effectiveness.…”
Section: Internal Audit Effectivenessmentioning
confidence: 99%
“…Research using agency theory (Xiangdong, 1997;Adams, 1994) and transaction cost theory (Spraakman, 1997) demonstrate internal audit's role in the management and governance of organisations. The literature (Dittenhofer, 2001) also discusses internal audit effectiveness and identifies basic tenets for its achievement.…”
Section: Literature Review and Focus Of The Studymentioning
confidence: 99%